The Bangwa Queen: Artifact or Heritage?. Issue 1 (9th May 2019) - Campfens, Evelien
Abstract: The return of cultural objects lost as a result of colonial rule is a controversial issue. A common response is: "it was legal at the time" and, therefore, not a legal issue. But is that so? This article argues that it is not a lack of legal norms that explains this belated discussion but, rather, the asymmetrical application of norms. Moreover, a human rights law approach, focusing on the heritage aspect of cultural objects for people today—instead of a sole focus on property title—offers useful tools to structure this field. To illustrate these points, a case concerning an African ancestral sculpture today known as the "Bangwa Queen" will be assessed on its merits under international law. The Bangwa Queen is of spiritual importance to the Bangwa, a people indigenous to the western part of Cameroon. She was taken as part of a collection of so-called lefem figures by German colonizers in 1899 and is currently part of a French museum collection.